Application of Bay’ Al-Salam in e-commerce transaction / Norhanisah Nordin - Nordin, Norhanisah (2019)
E-commerce has been recognized as a new form of transaction that uses an internet as a medium. People can choose and transact several of products in e-commerce. However, e-commerce may involve in fraudulent and safety issues due to a certain reasons like scam and human misconduct. The similarity of bay’ al-Salam and e-commerce should be proven by comparing these two issues in Islamic perspective. The aim of this research is to study the application of bay al-Salam rulings in e-commerce activities and to highlight a main fraud issues besides to suggest for a more secure e-commerce using bay’ al-Salam concept. This research will collect data based on literature review and a survey that be conducted to ACIS diploma student in UiTM Puncak Alam through a questionnaire. The data will be analyses on the respondent experience in e-commerce activities, a problem faced by them during online transaction and this research will also analyses on past research opinion and finding regarding bay’ al-Salam and related to e-commerce. The result of this research find out that bay al-Salam concept is similar to e-commerce and be applied in e-commerce activities from the aspect of product and others. However, this research also find out that a fraud issues in e-commerce still occur and should be avoid in order to realize a secure e-commerce through a right way and regulation to solve and prevent fraud. It is hope that this study will help to a more understanding and contribute to an improvement on e-commerce.